FMT intervention decreases urine 5-HIAA levels: a randomized double-blind controlled study - Wang, Lihong; Yu, Lianhu; Liu, Zhiyue; Che, Chao; Wang, Yu; Zhao, Yongheng; Zhu, Mengna; Yang, Guang; Cao, Aihua (Frontiers in Medicine, 2024)
Background: Autism Spectrum Disorder (ASD) is often linked to gastrointestinal issues and altered serotonin metabolism. Emerging evidence suggests gut microbiota influence both, with fecal microbiota transplantation (FMT) offering a potential therapeutic approach. However, its impact on serotonin metabolism and ASD symptoms is not well understood. In this study, we aimed to evaluate the clinical effects of FMT and examine changes in specific urinary metabolites in children with ASD.Methods: A randomized double-blind controlled trial was performed to evaluate the clinical effects of FMT on GI and ASD-related symptoms. Gastrointestinal symptoms were assessed using the Gastrointestinal Symptom Rating Scale (GSRS) and the ASD-related symptoms were assessed using the Childhood Autism Rating Scale (CARS), Aberrant Behavior Checklist (ABC), and Social Responsiveness Scale (SRS) scores. Urinary metabolites were analyzed by homogeneous enzyme immunoassay using commercially available kits. Results: Significant improvements in GI and core ASD symptoms were observed following FMT intervention. The average GSRS scores decreased from 30.17 (before) to 19 (after; p < 0.0001), CARS scores decreased from 36.22 to 33.33 (p < 0.0001), SRS scores decreased from 151.17 to 137.5 (p = 0.0002), and the ABC scores decreased 76.39 to 53.17 (p < 0.0001) in the FMT group. However, in the placebo group, GSRS, CARS, and SRS scores showed no significant changes, while ABC scores decreased from 72 to 58.75 (p = 0.034).The FMT group also showed a significant reduction in urinary 5-Hydroxyindoleacetic acid (5-HIAA) levels from 8.6 to 7.32 mg/L (p = 0.022), while other metabolites showed no significant changes.FMT is a safe and effective treatment for improving GI and core symptoms in children with ASD, with 5-HIAA showing potential as a urinary biomarker for treatment response.